uPAR-induced cell adhesion and migration: vitronectin provides the key - Madsen, Chris D. (The Rockefeller University Press, 2007)
Expression of the membrane receptor uPAR induces profound changes in cell morphology and migration, and its expression correlates with the malignant phenotype of cancers. To identify the molecular interactions essential for uPAR function in these processes, we carried out a complete functional alanine scan of uPAR in HEK293 cells. Of the 255 mutant receptors characterized, 34 failed to induce changes in cell morphology. Remarkably, the molecular defect of all of these mutants was a specific reduction in integrin-independent cell binding to vitronectin. A membrane-tethered plasminogen activator inhibitor-1, which has the same binding site in vitronectin as uPAR, replicated uPAR-induced changes. A direct uPAR–vitronectin interaction is thus both required and sufficient to initiate downstream changes in cell morphology, migration, and signal transduction. Collectively these data demonstrate a novel mechanism by which a cell adhesion molecule lacking inherent signaling capability evokes complex cellular responses by modulating the contact between the cell and the matrix without the requirement for direct lateral protein–protein interactions.